The Effect of Gadget Use on Child Development: A Path Analysis Evidence from Melawi, West Kalimantan - Calorina, Livia; Pawito, Pawito; Prasetya, Hanung (Journal of Maternal and Child Health, 2020)
Background: The use of gadgets in early childhood can affect the mental and physical deve